(Amino acid + silica) adsorption thermodynamics: Effects of temperature. (August 2015) - Sebben, Damien; Pendleton, Phillip
Graphical abstract: Highlights: High resolution, low concentration Gly, Lys and Glu solution adsorption isotherms. All isotherms fitted with Langmuir–Freundlich isotherm model. Gly, Lys and Glu show exothermic adsorption processes. Isosteric heat analyses reveal changes in interaction strength with surface coverage. Abstract: A thorough understanding of amino acid adsorption by mineral and oxide surfaces has a major impact on a variety of industrial and biomedical applications. Little information currently exists regarding temperature effects on most of these adsorption processes. Deeper thermodynamic analyses of their multiple temperature adsorption isotherms would aid the interpretation of the interfacial interactions. Low solution concentration adsorption isotherms for glycine, lysine and glutamic acid on a silica adsorbent were generated for T  = (291, 298 and 310) K. Data analysis via the Clausius–Clapeyron method yielded the isosteric heat of adsorption as a function of fractional monolayer coverage for each adsorptive. Each amino acid showed an exothermic adsorption response. Glycine and lysine experienced a greater negative effect of increased temperature compared with glutamic acid, indicating a greater number of adsorbed molecules than glutamic acid, with the former undergoing intermolecular clustering within the adsorbed phase. Isosteric heat analyses suggest ionic interactions for lysine and hydrogen bonding for glutamic acid, both weakening with increased coverage. In contrast, initial hydrogen bonding led to ionic bonding for glycine with increasing coverage.